(876) سياسة الزراعه المحميه وجدواها الاقتصادية من خلال مناقشات ممثلي الأمه في مجلس الشعب Protected agriculture policy and its economic feasibility through discussions of the nation's representatives in the People's Assembly - عيون عبدالقادر مطاوع (876, 2026)
ملخص